2016
DOI: 10.1371/journal.pntd.0004350
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei gambiense Infections in Mice Lead to Tropism to the Reproductive Organs, and Horizontal and Vertical Transmission

Abstract: Trypanosoma brucei gambiense, transmitted by the tsetse fly, is the main causative agent of Human African trypanosomosis in West Africa and poses a significant health risk to 70 million people. Disease progression varies depending on host immunity, but usually begins with a haemo-lymphatic phase, followed by parasite invasion of the central nervous system.In the current study, the tropism of T. b. gambiense 1135, causing a low level chronic ‘silent’ infection, was monitored in a murine model using bioluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…This observation is in line with the fact that trypanosomes can survive in the extravascular spaces of diverse organs such as the heart, the central nervous system, and the skin 15 , 16 , 17 . Experimental infections in animals confirmed that parasites may be undetectable in the blood but hidden in different organs and tissues 18 , 19 , 20 , 21 , including the skin, from where they can be ingested by tsetse flies 22 , 23 . It was only recently that researchers began to investigate the underlying host–parasite interaction mechanisms responsible for those latent infections.…”
Section: Human Reservoirmentioning
confidence: 96%
“…This observation is in line with the fact that trypanosomes can survive in the extravascular spaces of diverse organs such as the heart, the central nervous system, and the skin 15 , 16 , 17 . Experimental infections in animals confirmed that parasites may be undetectable in the blood but hidden in different organs and tissues 18 , 19 , 20 , 21 , including the skin, from where they can be ingested by tsetse flies 22 , 23 . It was only recently that researchers began to investigate the underlying host–parasite interaction mechanisms responsible for those latent infections.…”
Section: Human Reservoirmentioning
confidence: 96%
“…Instead, this parasite is transmitted among horses and other equids during mating (Claes et al 2005). Of note, vertical or perinatal transmission of trypanosomes other than T. b. equiperdum in the reproductive tissues has been reported (Griffin, 1983; Melendez et al 1993; Lindner and Priotto, 2010; Biteau et al 2016), although the role and relative importance of this mode of transmission in the field is not clear.…”
Section: The Animal Trypanosomiases: Distribution Transmission Hostmentioning
confidence: 99%
“…One striking example is T. equiperdum, which is hardly studied in comparison to other infections due to the fact that it causes a disease characterized by sexual transmission in horses, a feature so far not reported in mice. In fact, only a single report is available on experimental sexual transmission of trypanosomosis in mice, and this report is dealing with T. b. gambiense ( 86 ). However, whether sexual transmission of T. brucei gambiense is a real issue in human trypanosomosis, remains a matter of debate ( 87 ) and more species-specific research is needed to resolve these issues.…”
Section: Human Trypanosomosis In Africa Is Only Part Of the Problemmentioning
confidence: 99%